Assessing the risk of contaminated sediments during small dam removal projects in the Long Island Sound watershed - Alix, Katelyn; Fedorchuk, Nicholas; Breslin, Vincent; Hoehne, Gary; Hayton, Jam; Balbachan, Kayla (Abstracts with programs - Geological Society of America, 2025)
Keywords: Computer science; Contamination; Ecology; Environmental science; Geology; Geotechnical engineering; Hydrology (agriculture); Oceanography; Sound (geography); Watershed; dept.egm; dept.esc

Glacial and postglacial interpretation of Late Paleozoic sedimentation in a tectonically active mountain front in Paganzo Basin, Argentina - Colombi, Carina; Alonso-Muruaga, Pablo; Kusick, Allison; Isbell, John; Fedorchuk, Nicholas; Alarcón, Carlos; Limarino, Carlos (Journal of Palaeogeography, 2025)
The Guandacol Formation corresponds to glacial episode 4 of the "Late Paleozoic Ice Age" in western Gondwana. It represents the final glaciation of westernmost Gondwana and the beginning of deglaciation that swept across the supercontinent throughout the rest of the Paleozoic. A succession of transitional sedimentary facies associations characterizes the eastern outcrops of the Guandacol Formation. These facies associations are interlayered with several deposits of mass-transport complexes (MTC) and present the occasional opportunity to conduct a deep-time analysis of the effect of tectonism in what is interpreted to be glacially-influenced deposits. Six sedimentary facies associations were recognized in the lower part of the Guandacol Formation. Facies association 1 (interbedded diamictites, sandstones, and mudstones) overlies MTC 1 and is interpreted as sedimentation into a marine glacially-influenced outwash fan. Facies association 2 (ponded interbedded sandstones, mudstones, and diamictites) was deposited as subaqueous underflows/turbidites and debris flows covering the irregular paleotopography of MTC 2. Facies association 3 (white medium- to coarse-grained sandstones and conglomerates) represents a small deltaic system. Facies association 4 (rhythmites with dropstones and sandstones) was deposited in a partially ponded water body resulting from the collapse and paleotopography of MTC 3. Facies association 5 (coarsening-upward cycles of mudstones and sandstones) was deposited in prodelta to delta front environments. Finally, facies association 6 (conglomerates, sandstones, and mudstones) corresponds to the subaerial deltaic platform. The evolution of depositional environments suggests three glacially-linked stages: Stage 1 — Initial retreat of the nearby ice masses (facies association 1); Stage 2 — Further retreat of glaciers and the progressive decoupling between ice masses and sea (facies associations 2 and 3); and Stage 3 — Postglacial sedimentation dominated by deltaic progradation during highstand conditions (facies associations 4 to 6). The importance of the paleogeographic context is emphasized in which the tectonism triggered recurrent events of MTC that continually modified the topography and sedimentary patterns, interrupting and complicating the stratigraphy of the interpreted glacial and postglacial sedimentation.
Keywords: Diamictites; Front (military); Geology; Geomorphology; Glacial period; Mass transport complex; Oceanography; Paleontology; Paleozoic; Postglacial sedimentation; Sediment; Sedimentation; Structural basin; Tectonism; dept.esc; peer-reviewed